INNOVATIVE APPROACHES TO ADDRESSING EDUCATIONAL INEQUITIES LESSONS FROM INDONESIA'S REMOTE LEARNING PROGRAMS - Amin, Fakhry (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2024)
Educational inequities remain a significant challenge in Indonesia, particularly in remote and under-resourced areas. The advent of remote learning programs has presented new opportunities to bridge these gaps, especially during the COVID-19 pandemic. This study explores innovative approaches within Indonesia's remote learning initiatives aimed at addressing educational disparities. Through a comprehensive literature review and analysis of case studies, the research identifies key strategies and their effectiveness in promoting equitable access to quality education. Findings indicate that technology integration, community involvement, and adaptive learning methodologies play crucial roles in enhancing educational outcomes. Despite the progress, challenges such as limited internet access and insufficient teacher training persist. The study underscores the importance of targeted policies and sustainable practices to ensure the long-term success of remote learning programs. This paper provides valuable insights for policymakers, educators, and stakeholders aiming to mitigate educational inequities and foster inclusive education in Indonesia.